Microbial population dynamics and dehydrogenase activity in response to integrated use of zinc oxide and zinc solubilizers - ASH, MOUMITA; YADAV, JANARDAN; YADAV, JAY SHANKAR (The Indian Journal of Agricultural Sciences, 2020)
Soil microorganisms play a key role in nutrient transformation, nutrient cycling, organic matter decomposition, water movement and various other processes essential for maintaining soil quality. In view of scanty information, a pot experiment was carried out at the Department of Soil Science and Agricultural Chemistry, Institute of Agricultural Sciences, BHU, Varanasi, UP during kharif, 2018-19 to evaluate the effect of zinc solubilizers in combination with zinc oxide (ZnO) on microbial population dynamics and dehydrogenase activity of soil at 30 DAT, 60 DAT and after harvesting of rice. In this experiment, three different doses of ZnO (Z0=0, Z1=1.85, and Z2=3.7 mg kg-1) and three types of microbial inoculation, viz. No inoculation (M0), Enterobacter clocae strain ZnPSBJ-6 (M1) and zinc solubilizing fungi (M2) were employed in various combinations. It has found that at 60 DAT, inoculation of M1 resulted in 4.1% and 12.8% increase in soil bacterial count while treated with Z1 and Z2, respectively. Whereas, in the case of M2, the fungal count increased by around 40% and 48% at 30 DAT while treated with Z1 and Z2, respectively over Z0. After harvesting, the actinomycetes population increased significantly by 45.5% in Z1 treated soil. At 30 DAT, dehydrogenase activity increased significantly in M2 treated soil by 7.3% and 27.3% with increasing level of ZnO, i.e. from Z1 to Z2 over Z0.